2017
DOI: 10.1159/000477119
|View full text |Cite
|
Sign up to set email alerts
|

Stachydrine Protects Against Pressure Overload-Induced Cardiac Hypertrophy by Suppressing Autophagy

Abstract: Background: Autophagy is required for the maintenance of cardiomyocyte homeostasis. However, excessive autophagy plays a maladaptive role in pressure overload-induced heart failure. To identify mechanisms by which Stachydrine inhibits pressure overload-induced cardiac hypertrophy, we determined inhibitory activities against activation of NADPH oxidase, reactive oxygen species(ROS) production and excessive activation of autophagy. Methods: Stachydrine was administered intragastrically to Wistar rats after Trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 19 publications
3
42
0
Order By: Relevance
“…Besides thermogenesis and the regulation of ATP synthesis, there are two other primary hypotheses regarding the physiological roles of UCP3: the regulation of fatty acid oxidation and the reduction of the mitochondrial generation of ROS [28]. And previous study showed that myocardial hypertrophy was accompanied by increasing of ROS production [29, 30]. The downregulation of UCP3 has previously been reported in hypertrophic myocardium and heart failure [31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Besides thermogenesis and the regulation of ATP synthesis, there are two other primary hypotheses regarding the physiological roles of UCP3: the regulation of fatty acid oxidation and the reduction of the mitochondrial generation of ROS [28]. And previous study showed that myocardial hypertrophy was accompanied by increasing of ROS production [29, 30]. The downregulation of UCP3 has previously been reported in hypertrophic myocardium and heart failure [31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…The structures are shown in Figure 1. Some studies have shown that these ingredients influence the cardiovascular system (Cao et al, 2017;Gao, Chen, Liang, Xie, & Chen, 2015;Huang et al, 2017;Olaleye, Crown, Akinmoladun, & Akindahunsi, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Over several years, our group has screened natural compounds for treating osteoclast‐related diseases . Stachydrine (STA), a bioactive constituent extracted from a medicinal herb Leonurus heterophyllus Sweet, has extensive pharmacological properties, including antioxidant, anti‐inflammatory, anticancer and cardioprotective properties . Recent studies have reported that STA inhibits NF‐κB and MAPK pathways in different cell types .…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Stachydrine (STA), a bioactive constituent extracted from a medicinal herb Leonurus heterophyllus Sweet, has extensive pharmacological properties, including antioxidant, anti-inflammatory, anticancer and cardioprotective properties. [17][18][19][20] Recent studies have reported that STA inhibits NF-κB and MAPK pathways in different cell types. [20][21][22] As the NF-κB and MAPK pathways are crucial for osteoclastogenesis and because STA exerts inhibitory effects on these pathways, we hypothesized that STA may represent a novel candidate for treating osteoclast-related diseases by inducing the targeted suppression of osteoclastogenesis.…”
mentioning
confidence: 99%